Assessment of Driving Safety in Older Adults with Mild Cognitive Impairment - Anstey, Kaarin J. (J Alzheimers Dis, 2017)
Background: With population aging, drivers with mild cognitive impairment (MCI) are increasing; however, there is little evidence available regarding their safety. Objective: We aimed to evaluate risk of unsafe on-road driving performance among older adults with MCI. Method: The study was a cross-sectional observational study, set in Canberra, Australia. Participants were non-demented, current drivers (n = 302) aged 65 to 96 years (M = 75.7, SD = 6.18, 40% female) recruited through the community and primary and tertiary care clinics. Measures included a standardized on-road driving test (ORT), a battery of screening measures designed to evaluate older driver safety (UFOV(®), DriveSafe, Multi-D), a neurocognitive test battery, and questionnaires on driving history and behavior. Results: Using Winblad criteria, 57 participants were classified as having MCI and 245 as cognitively normal (CN). While the MCI group had a significantly lower overall safety rating on the ORT (5.61 versus 6.05, p = 0.03), there was a wide range of driving safety scores in the CN and MCI groups. The MCI group performed worse than the CN group on the off-road screening tests. The best fitting model of predictors of ORT performance across the combined sample included age, the Multi-D, and DriveSafe, classifying 90.4% of the sample correctly. Conclusion: Adults with MCI exhibit a similar range of driving ability to CN adults, although on average they scored lower on off-road and on-road assessments. Driving specific tests were more strongly associated with safety ratings than traditional neuropsychological tests.